2019
DOI: 10.1089/omi.2019.0075
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 Diabetes Mellitus is Associated with the Immunoglobulin G N-Glycome through Putative Proinflammatory Mechanisms in an Australian Population

Abstract: Type 2 diabetes mellitus (T2DM) is a common complex trait arising from interactions among multiple environmental, genomic, and postgenomic factors. We report here the first attempt to investigate the association between immunoglobulin G (IgG) N-glycan patterns, T2DM, and their clinical risk factors in an Australian population. N-glycosylation of proteins is one of the most frequently observed co-and posttranslational modifications, reflecting, importantly, the real-time status of the interplay between the geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 38 publications
(52 reference statements)
1
17
0
Order By: Relevance
“…Furthermore, protein-glycan interactions are also known to play a role in many processes affecting disease progression [ 5 ]. For instance, aberrant glycosylation is often present in patients with cancer [ 6 , 7 ], diabetes and inflammation [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, protein-glycan interactions are also known to play a role in many processes affecting disease progression [ 5 ]. For instance, aberrant glycosylation is often present in patients with cancer [ 6 , 7 ], diabetes and inflammation [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Diseases are also driven by many diverse factors, including genetic variants, epigenetic dysregulation and environmental influences. Glycosylation, among other post-translational modifications (PTMs), can reflect the real-time status of these complex interactions and can provide potential diagnostic and prognostic biomarkers for multifactorial diseases [ 8 , 10 ]. Glycosylation is known to be altered in the process of ageing.…”
Section: Introductionmentioning
confidence: 99%
“…Our data revealed that metabolic parameters related to insulin levels and insulin resistance signi cantly associate with two distinct N-glycan structures -FA2B and A2G2S2. Herein, the FA2B structure negatively associates with insulin levels, but the same structure has been previously found to be increased in type 2 diabetes [30,31]. This might be attributed to the fact that type 2 diabetes pathogenesis, apart from insulin resistance, also involves defects of insulin-producing β-cells, responsible for decreased insulin production and secretion.…”
Section: Discussionmentioning
confidence: 57%
“…The results above were largely in consistent with previous studies of IgG glycosylation profiles in type 2 diabetes and its related factors. Previous studies have reported that complex glycan structures with bisecting GlcNAc were highly associated with some inflammatory diseases, reflecting a body status of pro-inflammation [11,27]. IgG proteins were sensitive to biological inflammatory stress and the variation of IgG glycans could reverse its anti-inflammation function [28,29].…”
Section: Discussionmentioning
confidence: 99%